My Little Pony, tolerance is magic: Gender policing and Brony anti-fandom. Issue 1 (1st April 2015) - Jones, Bethan
'Creepy and immature'; 'paedophiles'; 'a freaking embarrassment'; and 'pathetic sissies [who] giggle like school girls' are all phrases which have been used to describe fans of My Little Pony. More specifically, they are all phrases which have been used to describe Bronies, male fans of the My Little Pony: Friendship is Magic (2010–) cartoon. Bronies are often a source of ridicule, both on forums like Reddit and 4chan, where scores of threads dedicated to 'Brony hate' have been posted, and within the more mainstream press which fails to understand why grown men might watch and engage with a children's show. Furthermore, criticisms aimed at Bronies commonly resort to gendered stereotyping: My Little Pony is pink and sparkly, things that men are not supposed to like. That Bronies disrupt traditional notions of gender makes them both objects of ridicule and a means by which the gendered voice of anti-fandom can be complicated. Discussions on anti-fandom and gender often focus on 'female' texts like Twilight (Meyer, 2005) and Fifty Shades of Grey (James, 2012). As Matt Hills (2012) points out in his analysis of Twilight anti-fandom, girls' desires are frequently attacked by cultural commentators and the mainstream media. However, in this article I argue that the realm of Brony fandom, and anti-fandom, is far more complex. I build upon the work of Jonathan Gray (2003) and Cornel Sandvoss (2005) by examining Brony anti-fandom, particularly in relation to its use of social media and its heavily gendered pathologizing of Bronies by both men and women.